Penyuluhan Pertanian dan Pembuatan Kompos Menggunakan Sisa Limbah Sayuran di Desa Kalibening, Kecamatan Dukun, Kabupaten Magelang - Nurmiyati Nurmiyati; Hilda Cahya Yolanda; Miske Harissa; Fintya Herlita; Verani Handayanti; Iqtironia Khalima (Universitas Sebelas Maret, 2021)
This agricultural extension aims to provide knowledge and skills in maked compost to farmers in Kalibening Village, Dukun District, Magelang Regency. In this counseling, an activity was also held to make a compost starter by the agricultural extension worker in Kalibening Village, and then it was reprocessed with vegetable waste as the basic material for compost by the 44 KKN UNS group. Compost is organic fertilizer which is the result of decomposition or decomposition of organic matter produced from the remains of living things such as plants and animals carried out by active microorganisms such as bacteria and fungi. This composting used the remaining vegetable waste in Kalibening Village, Dukun District, Magelang Regency which produced a lot of vegetable waste. based on the results of observations where it is seen that the potential of the village which produces a lot of vegetable waste, becomed the background for introducing the type of compost as a source of organic matter in farmers' gardens. The purpose of the service is to foster and direct the residents of the Kalibening Village to have the ability to make compost from vegetable waste. The conclusion of this community service is that after being given training on the proper and correct management of vegetable waste, the community can overcome the waste problems around it and it is hoped that the people of Kalibening Village could evaluate the management that has been carried out previously.